Collective, Collage, and Translative Authorship: Writing to and from Multilingual Europe - Jamie H. Trnka (Studies in 20th & 21st Century Literature, 2024)
Letters to Europe (2011) is a collectively authored, transnational literary engagement with Europe as an idea, a place, and a set of socio-political relationships. A print publication and performance, the ambivalent generic status of the Brussels-based project raises productive questions about how collective translation, transnational authorship, and multimedial performance strategies combine to advance new modes of aesthetic and political representation for subjects in transit in twenty-first century Europe. I argue for attention to multilingual and multimedial translations as sites of creative self-documentation on the part of mobile subjects as a critical counterpoint to state-sanctioned forms of documentality (Favorini). To that end, I show how collage as an aesthetic and editorial technique is used to assemble a visual and performative unity of multilingual texts; consider its implications for contemporary debates on language, culture, mobility and belonging in Europe and the EU; and explore the confluence of translation, document, and migration in innovative European literatures today.
Keywords: collage; documentary; epistolary; Europe; EU; migration; multilingualism; performance; translation